2004
DOI: 10.1207/s15328015tlm1601_10
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Evaluations of Lectures Attended in Person or From Rural Sites via Interactive Videoconferencing

Abstract: Level of satisfaction was high for most aspects of remote lecture attendance, although not quite as high as for in-person attendance. Improved technical reliability would likely increase remote attendee satisfaction. Overall, lecture attendance using videoconferencing was found to be an acceptable alternative to travel for medical students in rural clerkships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 8 publications
4
43
0
Order By: Relevance
“…However, whilst there may be no significant difference in medical student attendance of live or remote lectures (Mattick, Crocker, and Bligh 2007), the current study shows that the remote site experience may be qualitatively less satisfying due to the diminished degree of engagement with the lecturer and the home audience. Elsewhere, both medical and physiotherapy students have felt interactivity to be compromised to some degree in video-linked lectures (Raffelini 2006;Mohammed, Waddington, and Donnan 2007) and medical student satisfaction was not quite as high for remote lecture attendance as for in-person attendance (Callas et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, whilst there may be no significant difference in medical student attendance of live or remote lectures (Mattick, Crocker, and Bligh 2007), the current study shows that the remote site experience may be qualitatively less satisfying due to the diminished degree of engagement with the lecturer and the home audience. Elsewhere, both medical and physiotherapy students have felt interactivity to be compromised to some degree in video-linked lectures (Raffelini 2006;Mohammed, Waddington, and Donnan 2007) and medical student satisfaction was not quite as high for remote lecture attendance as for in-person attendance (Callas et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, whilst students might prefer a live lecture with the speaker present, they still valued the remote delivery highly enough to attend. A previous study concluded that lecture attendance using videoconferencing was found to be an acceptable alternative for medical students in distributed locations (Callas et al, 2004). Another concluded that digital lectures were a viable alternative to live lectures for delivering didactic presentations to a distributed network of students (Soloman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…9 Videoconference-based education for psychiatry registrars at the University of KwaZulu-Natal, South Africa Videoconference-based education is an integral component in many telehealth services in countries such as Australia 10 and include activities such as journal clubs, ward rounds, continuing and formal medical education. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies evaluating these activities have reported general satisfaction with the use of videoconferencing and no difference in educational outcomes compared to traditional face to face teaching. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Nelson R Mandela School of Medicine at the University of KwaZulu-Natal has increased the psychiatry registrar posts three-fold over the last three decades.…”
Section: Videoconference-based Teachingmentioning
confidence: 99%